The Concept of Homeland in the Uzbek People and its Expression in Proverbs - Nuraliyeva Sitora (Global Scientific Publishing, 2023)
This article provides information on how high the concept of "Motherland" is for the Uzbek people and how this concept is honored and considered sacred for them. It is reflected in the proverbs that have been passed down to the generation, as well as the problems and solutions when they are translated into English.
Keywords: the concept of “Motherland”; concept; proverbs; translating problems